Experiences of primary health care nurses regarding the provision of free health care services in the Northern region of the Limpopo Province - VO Netshandama; L Nemathaga; SN Shai-Mahoko (AOSIS, 2005)
The purpose of the study was to explore the experiences of primary health care nurses working in the clinics and health centres involved in the provision of free health care services. The research design followed was exploratory, descriptive and qualitative. The population of the study included all primary health care nurses working at the clinics and health centres in the Vhembe (northern) region of the Limpopo Province. The sampling method used was purposive for the samples of both the clinics and the nurses. The inclusion criteria for the nurses included experience of two or more years in providing primary health care. The inclusion criteria for the selection of clinics included being a busy clinic (a minimum of 2000 patients per month) with a staff establishment of four or more primary health care nurses. In conducting this research, ethical principles were taken into account. Data was collected from 23 participants in the Northern Region. The research question read as follows: What are your experiences regarding the provision of free health care services? An open coding method consisting of eight steps provided by Tesch's (1990:140-145) eight-step method of analysing data was used. The research findings revealed that the primary health care nurses working in the clinics experience feelings of failure to provide adequate primary health care services due to the increased workload, misuse of the service, and fear associated with lack of security in the clinics and health centres. The conclusions drawn from this research are that on the one hand a poor mechanism exists for the monitoring of the implementation of free health services, and on another hand, there has been misuse of the facilities by the community. The concept "free health care service" has been misinterpreted.